Changes in children’s diet and physical activity as perceived by their mothers: Impact of a health promotion intervention for mothers in a sub-urban area of Nepal - Oli, Natalia; Vaidya, Abhinav; Eiben, Gabriele; Krettek, Alexandra (Journal of Kathmandu Medical College, 2018)
Background: Unhealthy diet and physical inactivity contribute to the growing burden of cardiovascular diseases in Nepal. Lifestyle is formed in childhood and in the Nepalese context influenced mainly by mothers, it is to date unknown how influential mothers are. Objectives: To assess changes in children’s diet and physical activity as perceived by their mothers after a health promotion intervention. Methodology: The Heart-Health Associated Research, Dissemination and Intervention in the Community is a community trial conducted in the Jhaukhel-Duwakot Health Demographic Surveillance site, in Bhaktapur district of Nepal. We conducted a health promotion intervention on diet and physical activity targeted at mothers with children aged one to nine years old in August-November 2016. Duwakot was randomized as the intervention site and Jhaukhel as the control. We conducted a follow-up study after three months to determine the outcome of the intervention. Nine trained enumerators conducted door-to-door visits to all households with eligible mothers. We calculated mean, frequency and percent changes for children’s behavior. Results: As responded by mothers, children in Duwakot consumed more healthy snacks after the intervention compared to Jhaukhel. Children in Duwakot increased consumption of water and milk. Children’s consumption of packet juices and soft drinks was decreased by 30% and 4% respectively. There was 21% increment in the duration of outdoor playing among the children at Duwakot during follow-up. Conclusion: The Heart-Health Associated Research, Dissemination and Intervention in the Community that focused on mothers showed indirect positive impact on their young children’s diet and physical activity behavior. In future, the longterm effects of such intervention should be assessed.